Autobiographical Aspects of Milica Janković’s Fiction (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This paper analyses Milica Janković’s fiction in the light of postmodern theoretical considerations of autobiography or any other kind of écriture de soi. It refers to the concepts of ‘autobiographical pact’ (introduced by Philippe Lejeune), and ‘autofiction’ (Serge Doubrovsky’s controversial invention, which was created in response to Lejeune’s theory). Milica Janković’s modernist fictional works are approached from this specific postmodern perspective, which enables comprehension and interpretation of their autofictional aspects.
Keywords: autobiography; autofiction; fiction; reality; Milica Janković